Effects of Specific Carob (Ceratonia siliqua L.) Liquid Concentrate on Glucose Metabolism in Subjects with Prediabetes: A Randomized Double-Blind Controlled Clinical Trial. - Pérez-Piñero, Silvia; Muñoz-Carrillo, Juan Carlos; Herrera-Fernández, Cristina; Muñoz-Cámara, Macarena; Hernández-Aliaga, Almudena; Echepare-Taberna, Jon; Ávila-Gandía, Vicente; López-Román, Francisco Javier (Nutrients, 2026)
Background/Objectives: A 90-day randomized double-blind and placebo-controlled study was conducted to assess the effect of carob (Ceratonia siliqua L.) on glucose metabolism in subjects with confirmed prediabetes. Methods: The carob liquid concentrate containing inositols of the carob fruit (D-pinitol, myo-inositol, D-chiro inositol) was administered at a daily dose of 6.66 g, divided into two doses of 3.33 g each. Study variables included glucose- and insulin-related parameters obtained at fasting conditions and during a standard 2 h oral glucose tolerance test (OGTT) at baseline and after 45 and 90 days of administration of the study products. Results: The study population included 52 subjects (25 in the experimental group, 27 in the placebo group), 27 men and 25 women, with a mean age of 45.6 ± 13.9 years. Subjects who consumed the active product showed improvements in glycated hemoglobin (HbA1c) and glucose levels as compared with placebo (p < 0.001 of the time × group interaction). Fasting serum insulin showed within-group significant decreases in the experimental group, with insulin indexes (HOMA-IR and QUICKI) improving significantly in the experimental group only. In the OGTT, there were significant improvements in the AUC of glucose and insulin, as well as glucose peak in the experimental group only. The product was well tolerated and no adverse effects were recorded. Conclusions: The use of a specific carob-based liquid concentrate decreased HbA1c and glucose levels in subjects with prediabetes, which may suggest its potential clinical relevance in the prevention of the transition from prediabetes to overt type 2 diabetes.